Factibilidad para la exportación de maíz en granos a Colombia de la Exportadora Hidrovo Exphimusa, año 2014. - Chica Chica, Darwin Lizardo (2015)
This thesis aims to study the feasibility to export corn grain Colombia, through the implementation of methods, techniques and research sources in order to know if there is viability export the grass, so it was necessary to know the process exporting follows Hidrovo SA in relation to the marketing of maize, customs processes to be followed to supply companies Colombia when the export is initiated analyzed. With respect to demand for corn that country requires supply for industry as there companies which use the product for feedstock, but there is a shortage of corn export 350,002 tonnes by source of advisory council of corn in Ecuador. Economic and financial feasibility is established as the estimated revenue in the first year of 176.000,00 existing data is annual growth of 6% (inflation index Colombia), as economic studies demonstrating that undertaking that for the first year of operations net income is $ 95,954.83 this means that the company has great utility to face a financial event, so it proves to be wise to invest in the project to export corn to Colombia since added value for the company beyond the return on invested capital is generated as the net present value is 71466.04 and internal rate of return is 43% which is the return on investment. In short there is the feasibility to export maize from the Exporting Hidrovo SA, to the Republic of Colombia, existing economic, technological and human resources to its effect and a high demand for Colombian companies that require grass from Ecuador.